2D nanomaterials: graphene and transition metal dichalcogenides. (27th April 2018) - Zhang, Hua; Chhowalla, Manish; Liu, Zhongfan
Abstract : Guest editors Hua Zhang, Manish Chhowalla and Zhongfan Liu introduce the 2D nanomaterials: graphene and transition metal dichalcogenides themed issue of Chemical Society Reviews .